Eco-friendly concrete using by-products as partial replacement of cement - El-Nadoury, Wegdan W. (Frontiers in Materials, 2022)
The current challenge facing the construction industry is to produce sustainable concrete at the lowest feasible cost. One obstacle to that is the demand for an excessive amount of cement. The reduction of cement content can be achieved by its partial replacement with by-product materials that attain an appropriate pozzolanic index. Two by-products namely; Ceramic waste powder (CWP) and rice husk ash (RHA) are remarkably formed throughout tiles and rice production. Using these by-products in concrete as a partial substitution for cement reduces landfills, the cost of concrete, and climate change due to cement production. This paper investigates the effect of replacing 5, 15, 20, 25, and 30 % of cement with CWP. Varied proportions of RHA; 5, 10, 15, and 25 % were added to the mix with the optimum CWP. The concrete mixture was proportioned to produce M30-grade concrete. Properties of concrete were assessed concerning workability, compressive, splitting tensile, and flexural strength. The results are compared to conventional concrete with 0% replacement. Results identified that 20 % substitution of cement by CWP efficiently improves compressive, splitting tensile, and flexural strength. In addition, the combination of 20% CWP and 10% RHA is the best substitute proposing superior strength compared to the control concrete.